Changing realities in the Western Hemisphere and the role of the Caribbean Community nations in this dynamic hemispheric process - Ramdin, Albert ([CCS] [Georgetown]GY, 2009)
Present some key characteristics of current development in the Western Hemisphere and deals with the role of the Caribbean Community in this changing environment.